ANALISIS PERAN MEDIA SOSIAL DALAM MEMBANGUN KESADARAN MASYARAKAT TENTANG PENTINGNYA PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DESA - Riskiya Ruksah Ritonga; Safitriani Safitriani (JURNAL ILMIAH NUSANTARA, 2024)
The aim of this research is to analyze the role of social media in building public awareness about the importance of community participation in village development. This research uses a quantitative approach with a survey research type. The population studied was village communities in Medan City, with sampling using a Random Stratified Proportional technique based on age, gender, education level and access to social media. The sample consisted of 50 respondents, selected assuming unknown population proportions. The research was conducted in 5 villages which reflect the diversity of village characteristics in Medan City. The overall conclusion is that social media is proven to have a significant role in building public awareness about the importance of participation in village development in Medan City. This is proven by the positive and significant relationship between access and use of social media and the level of community awareness about village development programs and their level of participation in these programs.